A study of aridity and droughts in the climatic Spectrum of the south Indian region (MAUSAM, 1984)
The paper initially deals with the classification of the climates of the south Indian region employing water balance procedure. Since the main meteorological source of water supply to the Indian region is the southwest monsoon during the summer season, the moisture regime of the region has a strong seasonal aspect. An attempt has been made here to study the incidence of droughts in the climatic spectrum of the south Indian region since, there is a broad relationship between the type of drought and the pattern of climates. That droughts are a common feature of the dry climates only is a past saying, since it is now known that droughts can and do occur even in humid climates with equal frequency. The Category and the frequency of droughts reduce the output from agricultural crops together with changes in the vegetation pattern. Proneness of the different climatic types of the south Indian region to droughts is investigated by selecting one station from each zone of the climatic spectrum and plotting the yearly indices of aridity against years of record and categorizing the drought years as suggested by Subrahmanyam and Sastri (1969). Decennial frequency of drought years is then calculated at each station and graphically plotted to get an insight into drought occurrence in the various climatic zones of the south Indian region.